Sosialisasi Panduan Mata Kuliah Berpraktik Mahasiswa S-1 Prodi Pariwisata Universitas Terbuka Batam - Ngarbingan, Hubertina Karolina; Suryantari, Yulita (Civiliza Publishing, 2024)
There are some of the courses offered practice or practicum. Practical activities/practicum are carried out under the guidance of instructors/supervisors. Practical implementation aims to provide experience and application in the real situations for students regarding the concepts and theories studied in the book of materials. Students are expected to be able to apply concepts, principles, procedures, and skills in real or artificial situations in a programmed and guided or independent manner. However, implementation in the field still requires compatibility, especially between practitioners and informants. The problems faced by students of Tourism Study Program, Faculty of Economicy & Business, Universitas Terbuka, are difficult in doing the tasks given in the practical learning process. Therefore, the dissemination of practical course guidelines for the of Tourism Study Program, Universitas Terbuka Batam is aimed at increasing students' abilities in preparing, implementing, and reporting activities through practice. The method used in community service is a participatory approach, training & implementation, and an evaluation of practice results. The results obtained, through practical guidelines/procedures, students can increase their knowledge and skills through field experience on various matters related to creative tourism activities, especially understanding its implementation practices in several regions in Indonesia.